MRI-guided STN DBS in Parkinson's disease without microelectrode recording: efficacy and safety. Issue 4 (22nd June 2010) - Foltynie, T; Zrinzo, L; Martinez-Torres, I; Tripoliti, E; Petersen, E; Holl, E; Aviles-Olmos, I; Jahanshahi, M; Hariz, M; Limousin, P
Abstract : Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is a commonly employed therapeutic procedure for patients with Parkinson's disease uncontrolled by medical therapies. This series describes the outcomes of 79 consecutive patients that underwent bilateral STN DBS at the National Hospital for Neurology and Neurosurgery between November 2002 and November 2008 using an MRI-guided surgical technique without microelectrode recording. Patients underwent immediate postoperative stereotactic MR imaging. The mean (SD) error in electrode placement was 1.3 (0.6) mm. There were no haemorrhagic complications. At a median follow-up period of 12 months, there was a mean improvement in the off-medication motor part of the Unified Parkinson's Disease Rating Scale (UPDRS III) of 27.7 points (SD 13.8) equivalent to a mean improvement of 52% (p<0.0001). In addition, there were significant improvements in dyskinesia duration, disability and pain, with a mean reduction in on-medication dyskinesia severity (sum of dyskinesia duration, disability and pain from UPDRS IV) from 3.15 (SD 2.33) pre-operatively, to 1.56 (SD 1.92) post-operatively (p=0.0001). Quality of life improved by a mean of 5.5 points (median 7.9 points, SD 17.3) on the Parkinson's disease Questionnaire 39 summary index. This series confirms that image-guided STN DBS without microelectrode recording can lead to substantial improvements in motor disability of well-selected PD patients with accompanying improvements in quality of life and most importantly, with very low morbidity.